Oral health in patients with diabetes type 2: dental caries, periodontal disease and tooth loss - Pablo Juárez, Rolando (2007)
The aim of this study was to determine the relationship between bucco-dental health and the degree of metabolic control among type II non-insulin dependent diabetic mellitus subjects. Three hundred subjects were divided into two groups of 150: Group I, diabetic with metabolic control (glycosylated haemoglobin [HbA1c] < 8.0%) and Group II, diabetic without metabolic control (HbA1c ≥ 8.0%). Clinical examination included frequency of oral hygiene practices, periodontal status by using the Community Periodontal Index of Treatment Needs (CPITN), Caries Index Treatments Needs (CITN), and the number of missing teeth. A statistically significant positive correlation was observed between two bucco-dental health indicators (CITN and CPITN) and both the duration of the disease and the degree of metabolic control. The study indicated that diabetic subjects should improve their oral hygiene practices, discontinue cigarette smoking and control blood glucose levels.